Analysis of Hunting Tourism: a Case Study of Slovenia (Prlekija Region) - Boris Prevolšek; Timo Roškar; Maja Borlinič Gačnik (Studia Ecologiae et Bioethicae)
The exploration of hunting tourism reveals its multifaceted benefits, encompassing nature preservation and tourism expansion. This study delves into the dynamics and prospective trends within hunting tourism, specifically in Prlekija's administrative unit of Gornja Radgona, Slovenia. It commences with a comprehensive international comparative analysis, followed by insightful semi-structured interviews involving key stakeholders within the destination. Hunting tourism emerges as a pivotal facet of tourism within this locale, exhibiting substantial potential for further growth, particularly in terms of diversification, regional integration, and synergy with other tourism offerings. However, it's imperative to address the adverse impacts of hunting tourism on biodiversity. As a counterbalance, the study underscores the increasing global emphasis on sustainable variants of hunting tourism, such as wildlife photography, fostering a more conscientious approach to animal tourism practices.